Measurement of Radioactivity in Dust in the Air using Gamma-ray Spectroscopic Analysis - Sudi Ariyanto; Ko Noguchi (BATAN, 2004)
ABSTRACT Experiment on measurement of radioactivity in the air using gamma spectrometry has been done. He-40T filter paper was set-up on the air collector (stapler) at 0.5 1.5 meters from the ground. Duration of air collection was set for 1.5 hours and flow rate of the air passing through the filter was measured. The filter, then, was put at 3 cm from a HPGe detector. Measurement of radioactive in the filter used a MCA system. The system was set at 3000 seconds for the counting time. Data obtained from the experiment have shown that radioactive concentration of Pb-212 in the air was in the range of 6.11 x10-8 17.2 x10-8 Bq/cm3. ABSTRAK Pengukuran radioaktif di udara dilakukan dengan menggunakan spektrometri gamma. Kertas penyaring He-40T ditata pada kolektor udara setinggi 0.5-1.5 meter dari tanah. Pengumpulan udara dilakukan selama 1.5 jam dan kecepatan alir rata-rata udara yang melalui penyaring diukur. Penyaring kemudian di letakkan 3 cm dari detektor HPGe. Pengukuran radioaktif pada kertas saring menggunakan sistem MCA. Pengukuran dilakukan selama 3000 detik. Data eksperimen menunjukkan bahwa konsentrasi radioaktif Pb-212 di udara pada rentang 6.11 x10-8 17.2 x10-8 Bq/cm3.